Absence of c-Ki-ras gene mutation in malignant and premalignant Barrett's oesophagus. Issue 4 (August 1995) - Lagorce, C; Fléjou, J-F; Muzeau, F; Hénin, D; Potet, F
Abstract : Aims —To establish the prevalence of c-Ki- ras gene mutations in codons 12 and 13 in 28 surgically resected Barrett's adenocarcinomas and 18 associated preneoplastic lesions in Barrett's oesophagus. Methods —Mutations were detected using the polymerase chain reaction followed by restriction fragment length polymorphism analysis. Human colon carcinoma cell lines with well characterised mutations in codons 12 and 13 were used as positive controls and to test the sensitivity of the method. Results —c-Ki- ras gene mutations were not detected in any of the 28 specimens of Barrett's adenocarcinoma or in the 18 specimens of Barrett's oesophagus (nine non-dysplastic cases, three cases with low and six with high grade dysplasia). Conclusions —These results suggest that the c-Ki- ras gene is not involved in the development of cancer in Barrett's oesophagus.